Examining the Mediating Effect of Strategic Agility in the Relationship Between Intellectual Capital and Organizational Excellence in Jordan Service - Al-azzam, Zeyad Faisal; Irtaimeh, Hani Jazza’a (Universiti Utara Malaysia, 2018)
his study aims to investigate the effect of intellectual capital and strategic agility on organizational excellence in service sector of Jordan. A total of 550 questionnaires were collected from respondents who were chosen from a stratified random sampling. The results revial that intellectual capital and its dimensions, human capital, structural capital, and relational capital, have a significant impact on strategic agility as well as organizational excellence. Moreover, results reveal that strategic agility fully mediates the relationship between intellectual capital and organizational excellence. The findings of this study can have significant implications for the service sector of Jordan.